PELAKSANAAN PELAYANAN PRIMA PADA COFFE SHOP DI HOTEL PENGERAN PEKANBARU - Putra, Alfirza Kadriansyah; Arief, Andi M Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In this recent years, coffee becomes a trend. Drinking coffee in a coffee shop has been life style. As we can see, nowadays, there are a lot of coffee shops built, franchised from outside Indonesia and the local ones. Some of us do not realize that Javanese coffee has been famous since years ago. We can see the Java script computer program has a coffee cup logo. So, coffee has been very populer and we are familiar with it. Keywords :Coffee Shop, Life Style